2022
DOI: 10.3390/ijms232112952
|View full text |Cite
|
Sign up to set email alerts
|

The Arabidopsis thaliana–Streptomyces Interaction Is Controlled by the Metabolic Status of the Holobiont

Abstract: How specific interactions between plant and pathogenic, commensal, or mutualistic microorganisms are mediated and how bacteria are selected by a plant are important questions to address. Here, an Arabidopsis thaliana mutant called chs5 partially deficient in the biogenesis of isoprenoid precursors was shown to extend its metabolic remodeling to phenylpropanoids and lipids in addition to carotenoids, chlorophylls, and terpenoids. Such a metabolic profile was concomitant to increased colonization of the phyllosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 105 publications
0
3
0
Order By: Relevance
“…Root exudates and phytohormones play an important role in modulating microbial colonization of the root zone [ 51 ]. A recent study showed that the Arabidopsis thaliana mutant chs5 remoulded the profile of isoprenoid-derived metabolites (including monoterpenoids and sesquiterpenoids), which further impacted the specific recruitment of Streptomyces into the microbiota [ 52 ]. SA, a key immune regulator, also modulates colonization of the root microbiome by specific bacterial taxa, including Streptomyces and Bacillus [ 53 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Root exudates and phytohormones play an important role in modulating microbial colonization of the root zone [ 51 ]. A recent study showed that the Arabidopsis thaliana mutant chs5 remoulded the profile of isoprenoid-derived metabolites (including monoterpenoids and sesquiterpenoids), which further impacted the specific recruitment of Streptomyces into the microbiota [ 52 ]. SA, a key immune regulator, also modulates colonization of the root microbiome by specific bacterial taxa, including Streptomyces and Bacillus [ 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…The available N, P and K in soil were determined according to the previous literature [ 58 ]. Soil micronutrient concentrations were measured using the diethylenetriaminepentaacetic acid (DTPA) extraction method [ 52 ]. A total of 10 g of air-dried soil was mixed with 20 ml of DTPA extraction solution (0.005 M DTPA, 0.01 M CaCl 2 , 0.1 M triethanolamine, pH 7.3) by shaking for 2 h at room temperature.…”
Section: Methodsmentioning
confidence: 99%
“…For example, cytokinin has been reported to act as a signaling molecule that drives phyllosphere bacterial community assembly and increases disease resistance [32]. Graindorge et al (2022) revealed that the metabolic status of the plant is vital for the recruitment of Streptomyces into the microbiota [33]. This evidence indicates that the plant could favor specific microorganisms by releasing specific volatile compounds.…”
Section: Leaf Exudatesmentioning
confidence: 99%